The Effect of Love of Money, Machiavellianism, and Tax Rates on Tax Evasion - Zesmitha Kisman; Junaidi Junaidi (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of love of money, machiavellianism, and tax rates on tax evasion. The population in this study are taxpayers in Palopo City. The number of questionnaires processed in this study were 334 respondents. To test the hypothesis, the researcher used a structural equation modeling (SEM) approach using AMOS and SPSS software. The results of this study indicate that love of money has an effect on Machiavellianism in doing tax evasion, machiavellianism and tax rates have an effect on tax evasion, while love of money has no effect on tax evasion